Prognostic Factors and Recurrence Patterns in T4 Gastric Cancer Patients after Curative Resection - Zhu, Bao-Yan (J Cancer, 2019)
Background: To investigate prognostic factors and recurrence patterns in T4 gastric cancer (GC) patients after curative resection. Methods: Between January 2004 and December 2014, 249 patients with T4 gastric cancer undergoing curative resection were recruited. Patient characteristics, survival, prognostic factors and recurrence patterns were analyzed. Results: Our results showed that the median survival time (MST) for T4 gastric cancer after curative resection was 55.47 months, with 59.47 months for T4a (tumor perforating serosa) and 25.90 months for T4b (tumor invasion of the adjacent structure). Multivariate analysis indicated that age (hazard ratio [HR], 1.86; P = 0.006), location of tumor (HR, 1.25, 0.90 - 5.64; P < 0.001) and intraoperative blood loss (HR, 1.85; P = 0.010) were independent prognostic factors for overall survival (OS). After a median follow-up of 25.87 months, a total of 109 (43.8%) patients suffered from recurrence, and 90 patients had been observed specific recurrence sites, among which peritoneal metastasis was the most common recurrence pattern, 59.0% for T4a and 88.3% for T4b, respectively. Conclusions: For T4 gastric cancer patients after curative resection, older age, gastric cancer of the entire stomach and more intraoperative blood loss were associated with poor OS. The recurrence rate after curative resection for T4 was high, and the most common recurrence pattern was peritoneal metastasis.